2021
DOI: 10.3390/microorganisms9122427
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceuticals and Herbal Food Supplements for Weight Loss: Is There a Prebiotic Role in the Mechanism of Action?

Abstract: Numerous nutraceuticals and botanical food supplements are used with the intention of modulating body weight. A recent review examined the main food supplements used in weight loss, dividing them according to the main effects for which they were investigated. The direct or indirect effects exerted on the intestinal microbiota can also contribute to the effectiveness of these substances. The aim of this review is to evaluate whether any prebiotic effects, which could help to explain their efficacy or ineffectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 118 publications
1
12
0
Order By: Relevance
“…They demonstrated that among Buddhists and Muslims, the Prevotella enterotype dominates the gut microbiome, while in people of other religions, including Christians, the Bacteroides enterotype is the most common [ 15 ]. This is mainly due to the food components that characterize the different diets, especially based on their fibre content, which was also confirmed by the review proposed by Bertuccioli et al [ 16 ].…”
supporting
confidence: 66%
“…They demonstrated that among Buddhists and Muslims, the Prevotella enterotype dominates the gut microbiome, while in people of other religions, including Christians, the Bacteroides enterotype is the most common [ 15 ]. This is mainly due to the food components that characterize the different diets, especially based on their fibre content, which was also confirmed by the review proposed by Bertuccioli et al [ 16 ].…”
supporting
confidence: 66%
“…Corn also contains cryptoxanthin, a naturally occurring carotenoid pigment. Regular use of cryptoxanthin has been proven to reduce the incidence of lung cancer by 27% [35].…”
Section: Heart-attack and Lung-cancermentioning
confidence: 99%
“…As a worldwide epidemic, obesity can be defined as excessive body fat. Heart disease, coronary artery disease, high blood pressure, high cholesterol, respiratory illness, osteoarthritis, cancer, and infertility are all well-known risk factors [35,36].…”
Section: Obesitymentioning
confidence: 99%
“…Alternative therapies resulting from nutraceuticals or natural products have achieved more attention, and particular dietary components have been utilized to restrain obesity and its associated disorders. [12][13][14] Beta-glucan (BG) is one of the key active components of mushrooms and of other sources like yeast, cereals, and grass. 15 BG is a dietary fiber readily found and is a relatively inexpensive byproduct, and it is added to foods on the assumption that this will contribute to health benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative therapies resulting from nutraceuticals or natural products have achieved more attention, and particular dietary components have been utilized to restrain obesity and its associated disorders 12–14 . Beta‐glucan (BG) is one of the key active components of mushrooms and of other sources like yeast, cereals, and grass 15 .…”
Section: Introductionmentioning
confidence: 99%